Indexation of Unemployment Benefits to Previous Earnings, Employment and Wages - Burkhard Heer; Albrecht Morgenstern (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2000)
In most OECD countries, unemployment benefits are tied to individual previous labor earnings. We study the progressivity of this indexation with regard to its effects on employment, output and wages in four equilibrinin models of the labor market keeping the level of unemployment benefits fixed. In the two cases of competitive labor markets and decentralized wage bargaining, employment and output increase, while wages decrease with the degree of indexation. In the model with search unemployment and Nash wage bargaining, all wages, employment and output increase, while die indexation of employirient benefits to previous carnings has no effect in the case of efficiency wages. In addition, our results suggest that a more progressive mdexation of unemployment benefits to labor earnings is wellare enhancing.
urn:nbn:de:bvb:19-epub-30-4
Keywords: H57; M55; 330; Unemployment Benefits; Progressive Indexation; Union Wage-Setting; Search Unemployment; Efficiency Wages